A single-center experience of the nationwide daunorubicin shortage: substitution with doxorubicin in adult acute lymphoblastic leukemia. Issue 10 (October 2013) - Patel, Samit; Liedtke, Michaela; Ngo, Dat; Medeiros, Bruno C.
Abstract Due to a national shortage of daunorubicin we evaluated the effects of substituting doxorubicin 1:1 in the induction phase for adult patients with newly diagnosed acute lymphoblastic leukemia (ALL). We identified 10 patients receiving doxorubicin instead of daunorubicin as part of their induction on Cancer and Leukemia Group B (CALGB) 9511 or CALGB10403 and retrospectively compared them to 83 patients who received treatment on the same protocols with daunorubicin. Response rates were similar, independent of anthracycline received, with either CALGB9511 or CALGB10403. In either regimen, doxorubicin resulted in longer absolute neutrophil count (ANC) recovery time and hospitalization. Doxorubicin as part of CALGB9511 resulted in greater than three-fold higher mucositis. Sepsis and death during induction were significantly more frequent in patients who received doxorubicin on CALGB10403. While remission rates were similar, the use of doxorubicin was associated with prolonged neutropenia, higher risk of mucositis, infection and sepsis, and prolonged hospitalization. Higher induction mortality observed with doxorubicin substitution in this analysis needs further study.